The effects of pomegranate (punica granatum) extract in-vitro and in-vivo studies towards development of non-opioid substitution therapy - Norhaslinda Ridzwan
Pomegranate iPunica granatum) are the oldest known edible fruit produced in tropical and subtropical regions such as Mediterranean region, Afghanistan, Iran and other countries. Nowadays, there is an increased interest in this fruit as a functional food for health benetits because of its useful in disease prevention and wellne promotion. Studie